2012
DOI: 10.4111/kju.2012.53.4.253
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Zone Index and Intravesical Prostatic Protrusion in Benign Prostatic Hyperplasia Patients: Correlations according to Treatment Received and Other Clinical Data

Abstract: PurposeThe aim of this research was to assess the value of the transitional zone index (TZI) and intravesical prostatic protrusion (IPP) from transrectal ultrasonography in evaluating the severity and progression of disease by analyzing the relationship between the 2 parameters and symptoms, clinical history, and urodynamics in benign prostatic hyperplasia (BPH) patients undergoing different treatment.Materials and MethodsA total of 203 patients receiving medication and 162 patients who underwent transurethral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Q max⁥ and PSA appear not to be good indicators for progression of BPH. In the current study, we found that the control group has smaller prostate volume and lower level of I-PSS than the progression group ( P < 0.05), which agreed with the results from other studies [ 2 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Q max⁥ and PSA appear not to be good indicators for progression of BPH. In the current study, we found that the control group has smaller prostate volume and lower level of I-PSS than the progression group ( P < 0.05), which agreed with the results from other studies [ 2 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…This compares with mean volume of 10.6 cc in a Japanese screening study of asymptomatic men over age 55 years [16] and 9-15 cc in a population screening of Chinese men 40-70 years of age [17]. However, TZV reported in most studies in the United States and Asia in men of average age over 55 years ranges from 21-26 cc in subjects with TPV averaging 35-49 cc [6, 7, 15, 18,19,11,20,21]. Since TZV is known to correlate to TPV our results come as no surprise [22,4].…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that TZI accurately predicts acute urinary retention in BPH patients, and that it might be helpful to decide for medical therapy or surgery (16,17), and that it has a PPV for the progression and severity of the disease (18), and that it predicts the necessity of TUR-P procedure (19). It is confirmed that TZI and TZV predict the efficiency of TUR-P procedure pre-operatively (7), and that more than 60% of the TZV should be resected to benefit from TUR-P (20).…”
Section: Discussionmentioning
confidence: 99%